Pengaruh Induksi Magnet Permanen Dengan Empat Posisi Pada Dielectric Barrier Discharge - Mangapul, Toni; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Dielectric barrier discharge technology is widely used in various area as a technology for producing electric plasma. One of the uses of dielectric barrier discharge is to produce ozone. The dielectric barrier discharge configuration consists of two electrodes flanking two dielectrics, air dielectric and solid dielectric. Dielectric discharge occurs in the air gap called plasma. The resulting plasma is not only affected by discharge equipment, but can also be affected by external field effects such as UAV radiation and magnetic fields. This study uses a four position permanent magnet on the dielectric barrier discharge with the magnets located on the top and bottom sides of the electrodes as well as the right and left side of the air gap with three variations of magnetic conditions, namely variation I (Conditions of top and bottom magnet attraction and magnet attraction right and left), variation II (Conditions of top and bottom magnet attraction and repulsion of right and left magnet), variation III (Conditions of top and bottom magnet repulsion and attraction of right and left magnet). The research results showed the highest intensity in variation I. Discharge current obtained from testing was the variation I is greater than variation II and variation III. The results of testing the concentration of ozone dielectric barrier discharge four positions found that the highest ozone concentration in variation I while the lowest ozone concentration in variation III. Keyword: dielectric barrier discharge,plasma,ozon